HUBUNGAN PENGETAHUAN PERAWAT TENTANG ARITMIA DENGAN SIKAP PERAWAT DALAM PENANGANAN ARITMIA DI RUANGAN CVCU DAN IGD RSUD DR. ADNAAN WD PAYAKUMBUH - Lisa Fradisa; Ida Suryati; Kalpana Kartikaa; Veviola Fitri (Jurnal Kesehatan Tambusai, 2021)
Sudden death or commonly known as sudden cardiac death is defined as an unexpected death or death process that is too fast. About 93% of sudden deaths are caused by arrhythmias, meaning that deaths occur due to heart rhythm disturbances that cause blood circulation failure. The purpose of this study was to determine the relationship between knowledge of nurses about arrhythmias and attitudes of nurses in handling arrhythmias in the CVCU and IGD rooms at Dr. Adnaan WD Payakumbuh. This study uses a descriptive correlation method with a cross sectional approach.. The sample in this study was 34 respondents. The results of the statistical test of univariate analysis showed that the respondents had good knowledge (61.8%) and had a positive attitude (61.8%). The results of the bivariate test showed that there was a relationship between nurses' knowledge about arrhythmias and nurses' attitudes in handling arrhythmias p value = 0.000 (p 0.05). It was concluded that there was a relationship between nurses' knowledge about arrhythmias and nurses' attitudes in handling arrhythmias in the CVCU and IGD rooms at Dr. Adnaan WD Payakumbuh. Therefore, hospitals can provide opportunities for nurses to continue their education and schedule training for nurses who have not attended training and those who have attended training are expected to attend counseling about arrhythmias once a month which aims to increase knowledge and attitude of nurses in the management of arrhythmias. Keywords: Knowledge, Arrhythmia Management, Attitude